The political economy of reshoring: Evidence from the semiconductor industry - Richard Clark; Sarah Kreps; Adi Rao (PLoS ONE, 2025)
States have increasingly taken steps to reshore manufacturing by shifting production back home from abroad. Although the literature on responses to globalization is increasingly robust, scholars tend to focus on the political consequences of economic dislocations, the effectiveness of government policies intended to roll back globalization, and the macroeconomic consequences of such policies. Our research is among the first to study public attitudes toward reshoring, including the basis of support, demographic variation, and sensitivity to factors like consumer prices. We advance hypotheses about the role of national security considerations and economic self-interest in shaping why and under what conditions the public backs incentives and investments that bring manufacturing home. We field two pre-registered survey experiments to representative samples of the American public, finding that US citizens support reshoring in most cases, irrespective of political party. Only the prospect of severe price increases and reshoring from geographically proximate allies moderate these responses. Our findings advance literatures on reshoring and public attitudes toward economic relationships, with implications for policy as governments consider reshoring a range of industries from technology to pharmaceuticals.